A computational approach on studying the regulation of TGF-β1-stimulated Runx2 expression by MicroRNAs in human breast cancer cells. (October 2021) - Pranavkrishna, S.; Sanjeev, G.; Akshaya, R.L.; Rohini, M.; Selvamurugan, N.
Abstract: Background: Transforming growth factor-beta1 (TGF-β1) acts as a most effective growth inhibitor for normal epithelial cells. Loss of this anti-proliferative factor in breast tissues favors invasion and development of osteolytic metastases, aided by a master transcription factor, runt-related transcription factor 2 (Runx2). Several reports identified Runx2 regulation with the help of non-coding RNAs such as microRNAs (miRNAs) under physiological and pathological conditions. Methods: Using bioinformatics tools such as miRDB, STarMir, Venny, TarBase, a unique list of miRNAs that putatively target the 3′ UTR Runx2 was identified. Further, the expression patterns of those miRNAs at the precursor and mature levels were studied by RT-qPCR analyses. Following this, computational analyses using software like TransmiR and bc-GenExMiner v4.6 were done to speculate the miRNA's other target genes that indirectly regulate Runx2 activity in breast cancer. Results: There were 13 miRNAs that putatively target Runx2 identified using bioinformatics tools. Among these miRNAs, miR-5703 expression was significantly downregulated at both precursor and mature levels upon TGF-β1-treatment in human breast cancer cells. Computational analyses speculated an indirect targeting of Runx2 by miR-5703 by influencing multiple Runx2 regulatory signaling pathways including Jak/Stat, MAPK, Wnt/β-Catenin, Notch, BMP, and PKA pathways. Furthermore, a correlation of the expression profiles of the speculated genes and Runx2 with miR-5703 was depicted in triple-negative breast cancer patients. Conclusion: Identification of miR-5703 and its network for Runx2 regulation directly or indirectly in breast cancer cells could significantly advance our understanding of breast cancer-mediated bone metastasis. In addition, it would potentially pave the way for miRNAs to be used as biomarkers and therapeutic agents in cancer research. Highlights: Runx2 is a predicted bone metastasis factor reported earlier in human breast cancer. In-silico analyses predicted 13 miRNAs that putatively target Runx2. TGF-β1 downregulated the expression of mir-5703 in MDA-MB231 cells. miR-5703 was predicted to regulate Runx2 and its signaling pathways.